Robust power control methods for wind turbines using DFIG-generator - El Karaoui, Imane; Maaroufi, Mohammed; Bossoufi, Badre (Institute of Advanced Engineering and Science, 2019)
The purpose of this work is to present the advantages of the power control (active and reactive) of a wind energy system in order to improve the quality of the energy produced to the grid by presenting two control strategies applied to the conversion system of wind energy equipped with an asynchronous generator with dual power supply. Both techniques are studied and developed and consist of a field control (FOC) and a sliding mode control. They find their strongest justifications for the problem of using a nonlinear control law that is robust to the uncertainties of the model. The goal is to apply these two commands to independently control the active and reactive powers generated by the decoupled asynchronous machine by flow orientation. Thus, a study of these commands will be detailed and validated in the Matlab / Simulink environment with the simultaneous use of the